Psychology Of Religion And Its Role In The Formation Of Modern Personality - Abdurauf Dehqonov (Periodica Journal, 2025)
The article analyzes various psychological approaches to understanding the phenomena of religiosity and religion, and the reasons why people turn to it. The points of view of both classical and modern authors on this issue are considered. Based on the material of the conducted empirical research, some differences in the value and moral sphere of people with shaped religiosity from people with non-shaped religiosity are shown.
Keywords: psychology of religion; religiosity; value sphere